Exploring Instructors’ Experiences in Human Resource Development at the Vocational and Productivity Training Center in Sidoarjo - Jasmiarto, Dicky; Sudrajat, Arief (Journal of Southern Sociological Studies, 2026)
Improving the quality of human resources (HR) is an important requirement in facing the demands of the ever-evolving world of work and industry. The Sidoarjo Vocational and Productivity Training Center (BPVP) acts as a competency-based training institution in preparing a skilled and ready workforce. This study aims to analyze the experiences of instructors in improving the quality of human resources through vocational training at BPVP Sidoarjo. This study uses a qualitative method with a descriptive phenomenological approach based on Alfred Schutz's phenomenological theory. The research subjects include instructors from the smart creative, smart manufacturing, smart office, and cake and bakery majors. Data were collected through observation and in-depth interviews, then analyzed by tracing the instructors' motives for action, namely the because motive and the in-order-to motive. The results of the study show that instructors interpret their role not only as technical teachers but also as facilitators and mentors in shaping the competencies, work ethic, and readiness of participants. Instructors also face various social challenges during training. This study confirms that the success of improving human resource quality is greatly influenced by the ability of instructors to interpret their role and manage the social dynamics of training.